Exopolysaccharides From Streptococcus thermophilus ST538 Modulate the Antiviral Innate Immune Response in Porcine Intestinal Epitheliocytes - Mizuno, Hiroya; Tomotsune, Kae; Islam, Md. Aminul; Funabashi, Ryutaro; Albarracin, Leonardo; Ikeda-Ohtsubo, Wakako; Aso, Hisashi; Takahashi, Hideki; Kimura, Katsunori; Villena, Julio; Sasaki, Yasuko; Kitazawa, Haruki (Frontiers in Microbiology, 2020)
It was reported that exopolysaccharides (EPSs) from lactobacilli are able to differentially modulate mucosal antiviral immunity. Although research has described the ability of EPSs derived from Streptococcus thermophilus to modulate the mucosal immune system, their impact on antiviral immunity was less explored. In this work, we investigated the capacity of the EPS-producing S. thermophilus ST538 to modulate the innate antiviral immune response triggered by the activation of the Toll-like receptor 3 (TLR3) in porcine intestinal epitheliocytes (PIE cells). Moreover, in order to study the immunomodulatory potential of S. thermophilus ST538 EPS, we successfully developed two mutant strains through the knockout of the epsB or epsC genes. High-performance liquid chromatography and scanning electron microscopy studies demonstrated that the wild type (WT) strain produced as high as 595 g/ml of EPS in the skim milk medium, while none of the mutant strains (S. thermophilus ΔepsB and ΔepsC) were able to produce EPS. Studies in PIE cells demonstrated that the EPS of S. thermophilus ST538 is able to significantly improve the expression of interferon  (IFN-), interleukin 6 (IL-6), and C-X-C motif chemokine 10 (CXCL10) in response to TLR3 stimulation. The role of EPS in the modulation of antiviral immune response in PIE cells was confirmed by comparative studies of cell free culture supernatants and fermented skim milks obtained from S. thermophilus ΔepsB and ΔepsC. These results suggest that S. thermophilus ST538 could be used as an immunobiotic strain for the development of new immunologically functional foods, which might contribute to improve resistance against viral infections.